Population structure and real exchange rate: evidence from the OECD countries - Hassan, AFM Kamrul (Curtin University, 2010)
This thesis examines the relationship between population structure and the real exchange rate in 23 OECD countries over the period 1980–2006. The motivation for this research stems mainly from the Life-Cycle Hypothesis (LCH) of consumption and saving. According to this hypothesis people accumulate saving during their working age to guard against the fall in consumption during their old age, thus smooth consumption over the entire span of life. Therefore, the size of the population that is at the earning stage affect the saving of an economy. In open economy domestic saving plays significant role in determining capital flows. Excess saving causes capital outflow, whereas shortfall of saving causes capital inflows. Capital flows are related to the appreciation or depreciation of the real exchange rate of an economy.Capital flow is also affected by investment. Different cohorts of population affect investment differently. An increase in the labour supply raises return on capital by increasing marginal product of capital. Higher return causes capital inflow and real appreciation. Besides, demand for consumption goods from dependents also affects investment and capital flow, which influences the real exchange rate.This thesis hypothesizes that the population structure affects the real exchange rate by affecting capital flows through its influence on saving and investment. Accordingly, objective of this thesis is to examine the effect of population structure on the real exchange rate.The real exchange rate is modeled as a function of terms of trade, net foreign assets, government expenditure, interest rate differential and three demographic variables, namely, young dependents (population ages 0-14), working age population (population ages 15-64) and old dependents (population ages 65 and above). These cohorts are expressed as the percentage of total population. Unbalanced panel data method is used to examine the hypothesized relationship between population structure and the real exchange rate.The estimation result shows 1% increase in the share of working age people in total population appreciates the real effective exchange rate index by 0.85%. This positive influence indicates that by increasing labour supply higher working age (vii) population raises return on capital. Domestic saving falls due to lower wage caused by higher labour supply. Therefore, foreign capital flows in and appreciates the real exchange rate.In case of 1% increase in the share of old dependents in total population, real effective exchange rate index depreciates by 0.97%. Although not supported by the LCH, this finding is consistent with the recent empirical studies that old people run down their assets very slowly due to various reasons. Thus they contribute positively to saving and depreciate the real exchange rate by causing capital outflow.The case study on Australia shows that only the log of real effective exchange rate index, net foreign assets and working age population are I(1). Johansen cointegration analysis indicates that there is one cointegrating relationship among these three variables implying a long-run equilibrium relationship among these variables. Granger causality test shows that there is long-run causality running from the working age population and net foreign assets to the real exchange rate. However, short-run adjustment coefficients are found to be insignificant, leaving the correction of deviations of the real exchange rate from its long-run value undetermined.This study identifies an important determinant of the real exchange rate, namely population structure. As transition of population structure is a long-run phenomenon, it can be utilized to study the long-run behavior of the real exchange rate.